2013
DOI: 10.1111/jvp.12078
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic relationship of marbofloxacin against Pasteurella multocida in a tissue‐cage model in yellow cattle

Abstract: The fluoroquinolone antimicrobial drug marbofloxacin was administered to yellow cattle intravenously and intramuscularly at a dose of 2 mg/kg of body weight in a two-period crossover study. The pharmacokinetic properties of marbofloxacin in serum, inflamed tissue-cage fluid (exudate), and noninflamed tissue-cage fluid (transudate) were studied by using a tissue-cage model. The in vitro and ex vivo activities of marbofloxacin in serum, exudate, and transudate against a pathogenic strain of Pasteurella multocida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
1
14
2
Order By: Relevance
“…The AUC 24 TCF/MIC ratio for bactericidal effects in this study was different from previous study values of 31.29, 278.08 and 50.65 h for 3-log reductions [3, 22, 31]. These differences may by accounted for by examining the ex vivo PK/PD model.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The AUC 24 TCF/MIC ratio for bactericidal effects in this study was different from previous study values of 31.29, 278.08 and 50.65 h for 3-log reductions [3, 22, 31]. These differences may by accounted for by examining the ex vivo PK/PD model.…”
Section: Discussioncontrasting
confidence: 99%
“…The supernatants were stored at −20 °C. The concentrations of marbofloxacin in tissue cage fluid were determined using a Waters 2695 series high performance liquid chromatography (HPLC) system with fluorescence detection [13, 22]. The chromatographic separation was achieved on an Agilent BDS C18 column (250 mm × 4.6 mm; internal diameter, 5 μm) at 28 °C with a thermostat column oven (Agilent 1200 series).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, tissue cages implanted subcutaneously attract some attention for PKs and PDs studies, especially in a target animal of veterinary interest ( Clarke, 1989 ). Because subcutaneously implanted tissue cages allow for repeated sampling, this model has been used extensively to study the distribution of antimicrobials( Clarke, 1989 ) and ex vivo antibacterial effectiveness in animal species of direct veterinary interest ( Aliabadi and Lees, 2002 ; Potter et al, 2013 ; Shan et al, 2014 ). In addition, tissue cage model has been used to contain an infection to allow for in vivo studies of antibacterial effectiveness ( Greko et al, 2003a , b ) and MSW studies in presence of the host defenses ( Zhao and Drlica, 2001 ; Cui et al, 2006 ; Ni et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Marbofloxacin, a synthetic third-generation fluoroquinlone, is specifically developed for individual veterinary treatment with a broad spectrum of activity against most gram negative bacteria, gram positive bacteria, mycoplasmas , and some intracellular pathogens such as Chlamydia and Brucella species ( Spreng et al, 1995 ). For antimicrobial activity properties of marbofloxacin, studies reported the values of AUC 24h /MIC required three levels of antibacterial activity, e.g., bacteriostatic, bactericidal and virtual eradication by ex vivo PK/PD integrated model in different biological fluids, respectively, in species of veterinary interest( Aliabadi and Lees, 2002 ; Sidhu et al, 2011 ; Shan et al, 2014 ). However, to our knowledge, in vivo antibacterial activity of marbofloxacin against Pasteurella multocida has not been reported in target animal-calves.…”
Section: Introductionmentioning
confidence: 99%
“…haemolytica the ratio ranged from 0.012:1 to 2.5:1 (Shan et al, 2014;Illambas et al, 2013;Potter et al, 2013). These data from several sources suggest: first, that serum MIC values should be considered on both a drug-by-drug and bacterial species-by-species basis to allow for the inactive protein bound fraction; and second, corrected serum values may not be the same as, and therefore might be used in preference to, the broth MIC for application to prediction of dosage for some drugs.…”
Section: Growth Medium and Drug Potencymentioning
confidence: 98%